Extent at Which Vocational Guidance Influence Career Decision of Vocational and Technical Students - Amos Ochayi Onojah; Omotayo Olabo Obielodan; Adenike Aderogba Onojah; Olawale Sunday Koledafe; Faruq Adebayor Ishola; Aderele Shadrack Omotayo (Indonesian Journal Of Educational Research and Review, 2021)
Personal guidance centers on problems of personality, physical and emotional development, interpersonal relations and similar matters. But vocational guidance given to students may or may not influence their career after graduation. This study thus examined extent at which vocational guidance influence career decision of vocational and technical students. This is a descriptive research design of the survey type. 220 technical students were sampled all technical education students in Ilorin metropolis. Frequency count and mean were used answer the research questions and Hypothesis was tested with t-test at 0.05 level of significance. The findings established that vocational guidance has been able to influence career decision making of vocational and technical education students to a high extent. Also, there was no significant difference in the impact of vocational guidance on career choice of junior and senior vocational and technical education students. It was therefore recommended that Vocational and Technology Education students should be exposed to the importance of guidance services and what counseling is all about in order for them to make good career decisions.